2011
DOI: 10.1007/s11605-011-1530-x
|View full text |Cite
|
Sign up to set email alerts
|

Can Laparoscopic Pancreaticoduodenectomy Be Safely Implemented?

Abstract: LPD can be implemented in a high-volume pancreatic surgery center with acceptable oncologic and patient outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
92
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(100 citation statements)
references
References 23 publications
(18 reference statements)
6
92
1
1
Order By: Relevance
“…[17] 6.2/9 N/A 14.2%/0% N/A N/A 2.3/3.8 0%/0% 0 N/A Eom et al [18] 11.5/13.5 a 0 35.5%/24.2% N/A 9.7%/6.5% 3.95/6.15 a 9.7%/6.5% N/A N/A Kim et al [19] 10/16 a 0 24.7%/29% N/A 8.6%/14.3% 3/3 0 N/A N/A Matsumoto et al [20] 12.9/23.8 a 0 7.1%/21.1% N/A 0%/10.5% 3.0/3.4 0 N/A N/A Misawa et al [21] 10/16 a 0 N/A N/A 0%/22% 7.5/2 0%/0% N/A N/A Tang et al [22] 7/11 0 33.3%/0% N/A 22.2%/0% N/A 0%/0% 0%/0% N/A Teh et al [23] 6.2/10.6 a 0 16.7%/56.2% a 0 8.3%/6.2% 3.4/3.4 0%/0% N/A N/A Velanovich et al [24] 5/8 a N/A 20%/27% N/A 13%/13% N/A 20%/32% N/A N/A Fernández-Cruz et al [25] 6 pancreaticoduodenectomy. A summary of series that compare the pre-operative, intra-operative and post-operative factors and outcomes in MIPD and OPD at their institutions is shown in Tables 3 and 4 [35][36][37][38] .…”
Section: Oncologic Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…[17] 6.2/9 N/A 14.2%/0% N/A N/A 2.3/3.8 0%/0% 0 N/A Eom et al [18] 11.5/13.5 a 0 35.5%/24.2% N/A 9.7%/6.5% 3.95/6.15 a 9.7%/6.5% N/A N/A Kim et al [19] 10/16 a 0 24.7%/29% N/A 8.6%/14.3% 3/3 0 N/A N/A Matsumoto et al [20] 12.9/23.8 a 0 7.1%/21.1% N/A 0%/10.5% 3.0/3.4 0 N/A N/A Misawa et al [21] 10/16 a 0 N/A N/A 0%/22% 7.5/2 0%/0% N/A N/A Tang et al [22] 7/11 0 33.3%/0% N/A 22.2%/0% N/A 0%/0% 0%/0% N/A Teh et al [23] 6.2/10.6 a 0 16.7%/56.2% a 0 8.3%/6.2% 3.4/3.4 0%/0% N/A N/A Velanovich et al [24] 5/8 a N/A 20%/27% N/A 13%/13% N/A 20%/32% N/A N/A Fernández-Cruz et al [25] 6 pancreaticoduodenectomy. A summary of series that compare the pre-operative, intra-operative and post-operative factors and outcomes in MIPD and OPD at their institutions is shown in Tables 3 and 4 [35][36][37][38] .…”
Section: Oncologic Outcomesmentioning
confidence: 99%
“…The MIPD's rate of major morbidity in the series mentioned above ranges from 25%-48%, compared to 31% in OPD [50] . The rate of pancreatic fistulas is an important post-operative outcome and is reported in [36] N/A 20 N/A 31 21.9/22.9 NS N/A 80%/83.9% 656.6/554.6 376.6/1509.5 a 0 Zureikat et al [37] 14 N/A N/A 14 28.5/30 NS N/A 0/0 456/372 a 300/400 14% Cho et al [38] N [36] N/A N/A NS N/A 45%/39% N/A 0/12.9% N/A N/A Zureikat et al [37] 8/8. [38] 16.4/15.…”
Section: Post-operative Recoverymentioning
confidence: 99%
“…Technical progress in LPD was achieved by several pioneering laparoscopic surgeons, including hand-assisted LPD [9,10] as well as laparoscopically assisted [11,12] and robot-assisted PD [13]. However, some surgeons have recently reported favorable outcomes [14][15][16][17]. LPD has not been accepted as a generalized surgical method for the resection of pancreatic head lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic pancreatoduodenectomy (LPD) was described first by (43)(44)(45). DOS was significantly shorter in several comparative studies (6 to 8 vs. 9 to 12.4 days, respectively) (40,43,44) whereas other studies (7,41) found no statistically significant difference. Conversion to open surgery was reported in 9.1% to 30.0% of cases, mostly due to venous invasion and intraoperative bleeding (7,44,46).…”
Section: Pancreatoduodenectomy (Pd)mentioning
confidence: 99%